2019
DOI: 10.1097/phh.0000000000000889
|View full text |Cite
|
Sign up to set email alerts
|

Control of Lead Sources in the United States, 1970-2017: Public Health Progress and Current Challenges to Eliminating Lead Exposure

Abstract: Context: During the past 45 years, exposure to lead has declined dramatically in the United States. This sustained decline is measured by blood and environmental lead levels and achieved through control of lead sources, emission reductions, federal regulations, and applied public health efforts. Objective: Explore regulatory factors that contributed to the decrease in exposure to lead among the US population since 1970. Design/Setting: We present historical information about the control of lead sources and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
152
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(152 citation statements)
references
References 20 publications
0
152
0
Order By: Relevance
“…The only significant risk factor was regularly eating with fingers/ hands (p<0.001). comparison, in developed countries where lead prevention programs have been active for decades, the prevalence of EBLLs is as low as 1.3% 14 . This study found significantly more boys had EBLLs compared to girls.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The only significant risk factor was regularly eating with fingers/ hands (p<0.001). comparison, in developed countries where lead prevention programs have been active for decades, the prevalence of EBLLs is as low as 1.3% 14 . This study found significantly more boys had EBLLs compared to girls.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, demographic data and thirty questions related to lead exposure risks, such as the presence of peeling paint in the dwelling, proximity to construction or busy roads, and the use of traditional medicines were asked. These questions were developed based on other studies as well as local context [12][13][14] .…”
Section: Data Collectionmentioning
confidence: 99%
“…The banning of leaded gasoline dramatically improved blood lead levels among people of all ages and has significantly reduced lead in the air [85]. Yet, the CAA falls short in protecting communities from lead exposure.…”
Section: Resultsmentioning
confidence: 99%
“…The Standards continue to focus on lead-based paint, as they are only applicable to homes built pre-1978, the year during which lead-based paint was outlawed. In doing so, the Standards overlook other historical sources of lead, such as lead from gasoline emissions, which was not completely phased out until the mid-1990s [85]; and lead in soil and dust that may be influenced by leaded paint.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation